2012
DOI: 10.1007/s12010-012-9560-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wort Gravity and Nitrogen Level on Fermentation Performance of Brewer’s Yeast and the Formation of Flavor Volatiles

Abstract: Normal gravity wort and high gravity wort with different nitrogen levels were used to examine their effects on the fermentation performance of brewer's yeast and the formation of flavor volatiles. Results showed that both the wort gravity and nitrogen level had significant impacts on the growth rate, viability, flocculation, and gene expression of brewer's yeast and the levels of flavor volatiles. The sugar (glucose, maltose, and maltotriose) consumption rates and net cell growth decreased when high gravity wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 31 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…Beers obtained from worts with higher percentages of glucose and fructose have higher ester levels than those obtained from maltose-rich worts. It has been suggested that glucose and fructose stimulate the glycolytic pathway and eventually lead to high levels of cytoplasmic acetyl-CoA, while maltose-rich wort only weakly induces acetyl-CoA formation [16]. Moreover, glucose induces ATF1 and ATF2 expression [13].…”
Section: Wort Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beers obtained from worts with higher percentages of glucose and fructose have higher ester levels than those obtained from maltose-rich worts. It has been suggested that glucose and fructose stimulate the glycolytic pathway and eventually lead to high levels of cytoplasmic acetyl-CoA, while maltose-rich wort only weakly induces acetyl-CoA formation [16]. Moreover, glucose induces ATF1 and ATF2 expression [13].…”
Section: Wort Compositionmentioning
confidence: 99%
“…It has been suggested that high nitrogen wort induces the transcription of BAT1 and ATF1, thus, increasing both higher alcohols and acetate ester synthesis [16]. This efect is even more pronounced in the presence of elevated concentrations of valine, isoleucine, and leucine, which are known precursors of higher alcohol synthesis via the Ehrlich pathway.…”
Section: Wort Compositionmentioning
confidence: 99%
“…In addition, treating wort with proteases increased the levels of FAN, leading to elevated concentrations of higher alcohols and esters during either high‐gravity brewing or normal‐gravity brewing by lager brewing yeast strains . Moreover, the wort FAN content can affect the transcription of both ATF1 and BAT1 genes, which are reported to strongly correlate with ester and higher alcohol synthesis, respectively . This suggests that the adjustment of FAN is a factor that can influence beer flavour.…”
Section: Introductionmentioning
confidence: 99%
“…Differential retention and loss of maltotriose consumption in S. pastorianus lineages may reflect different brewing process conditions during domestication. In modern brewing processes based on high-gravity wort, cell division is largely constrained to the glucose and maltose phases, which occur before depletion of nitrogen sources (Lei et al 2012). It may be envisaged that, in early lager-brewing processes, unstandardized mashing processes generated wort with a higher maltotriose content, which would have allowed for continued yeast growth during the maltotriose consumption phase.…”
Section: Discussionmentioning
confidence: 99%